A Novel Approach to Explore Edhi Foundation Knowledge for Ontology Construction - Raza, Muhammad Ahsan; Rahmah, Mokhtar; Qaswar, Fahad; Roslina, Abd Hamid; Raza, Sehrish (IJCSNS, 2020)
The worth of the Edhi Foundation (EF) system depends on how well its structural knowledge can be extracted by EF users and staff to perform daily activities. Ontology has emerged as a semantic tool to represent the knowledge of a particular domain and thus is a good choice for the semantic organization of EF data. However, building an ontology that suits the needs of EF users is a challenging task. This study presents a novel approach that uses the UML class diagram (UCD) to construct an ontology for the EF system. We propose UCD-to-ontology transformation rules, that is, the ontology model that is used for eliciting OWL ontology. We test our approach for the successful interpretation of UCD features to OWL ontology elements and find that the system performs well with an average precision of 97.80%.